2021
DOI: 10.1111/azo.12398
|View full text |Cite
|
Sign up to set email alerts
|

Tiny steps towards greater knowledge: An osteological review with novel data on the Atlantic Forest toadlets of the Brachycephalus ephippium species group

Abstract: Brachycephalus is a small, endemic genus of anurans that occur throughout the Brazilian Atlantic Forest. Recent analyses corroborated the monophyly of two species groups within this genus (B. ephippium and B. pernix), whereas the B. didactylus group appears to be polyphyletic. Herein, we compare and describe the skeletal system of all species from the Brachycephalus ephippium species group. We investigated diagnostic characters that are potentially useful to delimit similar species, confirmed the previously pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In the B. ephippium group, species have remarkably ossified skulls and vertebral columns, sometimes with a bony dorsal shield, and bone sculpturing consisting of ridges and crests inducing a reticulated or pitted pattern in the skull, spinal processes of sacral, and presacral vertebrae [20,25]. In contrast, in the B. pernix group, such hyper-ossification is not observed [19,20,27]. This might indicate that the bufoniform appearance of these toadlets is ontogenetically based on different developmental processes, which would be in agreement with an independent evolutionary origin.…”
Section: Evolution and Biogeography Of Brachycephalusmentioning
confidence: 99%
See 1 more Smart Citation
“…In the B. ephippium group, species have remarkably ossified skulls and vertebral columns, sometimes with a bony dorsal shield, and bone sculpturing consisting of ridges and crests inducing a reticulated or pitted pattern in the skull, spinal processes of sacral, and presacral vertebrae [20,25]. In contrast, in the B. pernix group, such hyper-ossification is not observed [19,20,27]. This might indicate that the bufoniform appearance of these toadlets is ontogenetically based on different developmental processes, which would be in agreement with an independent evolutionary origin.…”
Section: Evolution and Biogeography Of Brachycephalusmentioning
confidence: 99%
“…Surprisingly, early molecular phylogenetic evidence (Figure 2A) suggested that these two morphological groups are not reciprocally monophyletic within Brachycephalus [18]. Based on DNA sequences of few mitochondrial and two nuclear-encoded genes (tyrosinase and recombination activating gene 1), two major clades of pumpkin-toadlets were recovered: the B. ephippium group (with 15 species), characterized by a gradient of increased mineralization in the skull [20,[24][25][26][27], and the B. pernix group (with 19 species), which is not hyperossified [18][19][20]. The B. ephippium group is distributed across the Serra do Mar and Serra da Mantiqueira mountain ranges whereas the B. pernix group is distributed across the Serra do Mar, respectively at the north and south of the Guapiara Lineament [19] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%